2016
DOI: 10.1504/ijmc.2016.073358
|View full text |Cite
|
Sign up to set email alerts
|

Examining social influence factors affecting consumer continuous usage intention for mobile social networking applications

Abstract: Due to the rapid increase in the use of mobile devices, mobile socialnetworking applications (MSNAs) have proliferated during recent years. MSNAs can provide social groups with a means to communicate among group members. Although studies have shown that social influence is relevant to individual and group collective behaviour, few studies have investigated the predictive relationships between multiple integrated social influence factors and the behavioural intention for the use of MSNAs. Therefore, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
(64 reference statements)
4
20
0
Order By: Relevance
“…The research of U&G by Katz et al (1973) had observed interchangeability of print and broadcast media that can be applied to social media in the digital context. This standard of consumer behaviour was agreed by several authors that the gratifications of the media users and their intentions of using social media apps are strongly dependent on peer recommendation and the access to interactivity (Logan, 2016;Oh et al2015;Wang & Chou, 2016). This study further identified several usage habits by social media influencers (SMIs) that are perceived as elements of gratification for the media users or predicted intention to use the hashtags featured in the posts available.…”
Section: Cognitionsupporting
confidence: 66%
“…The research of U&G by Katz et al (1973) had observed interchangeability of print and broadcast media that can be applied to social media in the digital context. This standard of consumer behaviour was agreed by several authors that the gratifications of the media users and their intentions of using social media apps are strongly dependent on peer recommendation and the access to interactivity (Logan, 2016;Oh et al2015;Wang & Chou, 2016). This study further identified several usage habits by social media influencers (SMIs) that are perceived as elements of gratification for the media users or predicted intention to use the hashtags featured in the posts available.…”
Section: Cognitionsupporting
confidence: 66%
“…The TRA has been fruitfully employed in the previous studies to investigate the background of coupon usage, online shopping channel selection, social media applications use, and consumer buying intention in numerous contexts (Shimp & Kavas, 1984;Valentini et al, 2011;Wang & Chou, 2016). By using TRA, Wang and Chou (2016) determined that injunctive norms, descriptive norms, and social identity are associated positively to sustain the intention of mobile social networking applications. On the same note, Zhang and Ip (2015) assessed the association between customers' trust on social media advertising and customers' purchase intention using TRA.…”
Section: Theoretical Background and Hypothesis Development Theoreticamentioning
confidence: 99%
“…Social influence may derive from superiors, peers, subordinates and professional population (Wang et al, 2013). Wang and Chou (2016) noted that social influence includes four factors: injunctive norms, descriptive norms, social identity, and group norms.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%